2023
DOI: 10.1111/brv.12970
|View full text |Cite
|
Sign up to set email alerts
|

Common mechanisms of physiological and pathological rupture events in biology: novel insights into mammalian ovulation and beyond

Abstract: Ovulation is a cyclical biological rupture event fundamental to fertilisation and endocrine function. During this process, the somatic support cells that surround the germ cell undergo a remodelling process that culminates in breakdown of the follicle wall and release of a mature egg. Ovulation is driven by known proteolytic and inflammatory pathways as well as structural alterations to the follicle vasculature and the fluid‐filled antral cavity. Ovulation is one of several types of systematic remodelling that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 215 publications
0
2
0
Order By: Relevance
“…We propose that the increased rigidity it imparts to the GC-layer is key. During ovulation, contractile activity and ECM proteolysis facilitate the release of the cumulus-oocyte complex (COC) from the rupture site [15]. However, we observed in Movie 7 that the rupture site is smaller than the size of the COC, resulting in deformation upon exit.…”
Section: Discussionmentioning
confidence: 89%
“…We propose that the increased rigidity it imparts to the GC-layer is key. During ovulation, contractile activity and ECM proteolysis facilitate the release of the cumulus-oocyte complex (COC) from the rupture site [15]. However, we observed in Movie 7 that the rupture site is smaller than the size of the COC, resulting in deformation upon exit.…”
Section: Discussionmentioning
confidence: 89%
“…In fetal ovaries, exposure to dexamethasone increased FKBP5 ( Poulain et al, 2012 ), and overexpression of FKBP5 was associated with chemoresistance in ovarian cancer cells ( Sun et al, 2014 ), suggesting that ovarian FKBP5 is involved in the ovarian response to xenobiotic exposure. DDX3X was increased by ZEN in HS gilt ovaries and is involved with cell survival and cell cycle control in embryonic development ( Li et al, 2014 ) and is also identified as being a potential regulator of ovulation ( Zaniker et al, 2023 ). As an indicator of ZEN-induced oxidative stress in gilt ovaries during HS, MGST1 is increased in oocytes from endometriosis patients ( Ferrero et al, 2019 ), and is increased by antioxidant treatment of PCOS in rats ( Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%